An umbrella review of systematic reviews with meta-analyses evaluating positive and negative outcomes of Hydroxychloroquine and chloroquine therapy. (February 2021) - Celotto, Stefano; Veronese, Nicola; Barbagallo, Mario; Ometto, Francesca; Smith, Lee; Pardhan, Shahina; Barnett, Yvonne; Ilie, Petre Cristian; Soysal, Pınar; Lagolio, Erik; Kurotschka, Peter Konstantin; Tonelli, Roberto; et al.
Highlights: Hydroxychloroquine (HCQ) and chloroquine (CQ) are anti-malarial drugs frequently used in the rheumatologic field. The present study aimed to map and grade the diverse health outcomes associated with HCQ/CQ using an umbrella review approach. There is high evidence of the efficacy of HCQ/CQ in the rheumatologic field. The lack of evidence for efficacy and the risk of death associated with the use of HCQ/CQ for COVID-19 indicate the urgent need for randomized controlled trials to determine their eventual appropriateness as a COVID-19 therapy. Abstract: BACKGROUND & AIMS: Hydroxychloroquine (HCQ) and chloroquine (CQ) are anti-malarial drugs frequently used in the rheumatologic field. They were recently identified as potential therapeutic options for Coronavirus Disease (COVID-19). The present study aims to map and grade the diverse health outcomes associated with HCQ/CQ using an umbrella review approach. METHODS: Umbrella review of systematic reviews of observational and intervention studies. For observational studies, random-effects summary effect size, 95% confidence interval, and 95% prediction interval were estimated. We also assessed heterogeneity, evidence for small-study effect, and evidence for excess significance bias. The quality of evidence was then graded using validated criteria from highly convincing to weak. The evidence from randomized controlled trials (RCTs) was graded using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) tool. RESULTS: From 313 articles returned in the literature search, six meta-analyses were included (n = 25 outcomes). Among meta-analyses (MAs) of observational studies, HCQ/CQ are weakly associated with a reduced risk for cardiovascular events and diabetes when used for autoimmune diseases and with spontaneous abortion; they are also associated with a higher risk of death in COVID-19 patients. Among MAs of RCTs, HCQ/CQ are associated with an improvement of articular manifestations of rheumatic diseases. CONCLUSIONS: There is high evidence of the efficacy of HCQ/CQ in the rheumatologic field. The lack of evidence for efficacy and the risk of death associated with the use of HCQ/CQ for COVID-19 indicate the inappropriateness of their inclusion in recent COVID-19 therapy guidelines and the urgent need for RCTs to determine eventual appropriateness as a COVID-19 therapy.